Employment and Economic Well-Being of People With and Without Disabilities Before and After the Great Recession. (September 2015) - Livermore, Gina A.; Honeycutt, Todd C.
The latest U.S. economic recession, commonly referred to as the Great Recession, has had a far-reaching impact, but its effects may be disproportionately experienced by working-age people with disabilities, given their already tenuous attachment to the labor force. We used data from the Current Population Survey both to describe the experiences of working-age people with disabilities during 2006–2012 (a period beginning before and ending after the Great Recession) and to compare the experiences of this population with those of working-age people without disabilities. We found few significant differences in the characteristics of people with disabilities before and after the Great Recession. The employment rate of people with disabilities was low both before and after the recession, though the decline in employment among people with disabilities was somewhat greater than for people without disabilities. The employment declines observed during this period for people with disabilities reflect a long-term downward trend that has persisted for decades, raising concerns that people with disabilities are permanently exiting the labor force. Job loss after the recession was particularly concentrated among people with disabilities in blue-collar and goods-producing jobs. People with and without disabilities experienced similar increases in poverty. Ongoing surveillance of the characteristics and employment of people with disabilities is needed to identify trends and develop policies to promote their independence and economic security.